The “Sandwich Generation” Revisited: Global Demographic Drivers of Care Time Demands - Diego Alburez-Gutierrez; Carl Mason; Emilio Zagheni (Population and Development Review, 2021)
Generational overlap affects the care time demands on parents and grandparents worldwide. Here, we present the first global estimates of the experience of simultaneously having frail older parents and young children (“sandwichness”) or young grandchildren (“grandsandwichness”) for the 1970–2040 cohorts, using demographic methods and microsimulations. We find that sandwichness is more prevalent in the Global South—for example, almost twice as prevalent in sub-Saharan Africa as it is in Europe for the 1970 cohort—but is expected to decline globally by one-third between 1970 and 2040. The Global North might have reached a peak in the simultaneous care time demands from multiple generations but the duration of the grandsandwich state will increase by up to one year in Africa and Asia. This increasing generational overlap implies more care time demands over the entire adult life course, but also opens up an opportunity for the full potential of grandparenthood to materialize.
Keywords: 300